(untitled) (The South East European Journal of Economics and Business, 2023)
This study aimed to investigate determinants of purchase cheeses with GIs in developing country and to ana- lyze to what extent these factors affected individuals’ purchasing intention, because there is a growing inter- est in geographical indications of origin (GIs) as a tool for product differentiation. An extension of the theory of planned behavior (TPB) is used as the framework of the study. To get a deeper insight into the influence of unobserved exogenous latent variables on consumers’ intentions to purchase GI cheeses, SEM and Logit models were combined and the SEM-Logit integration model was constructed. The study supports extended model of TPB, which includes trust and loyalty, as a useful framework to understand the consumers’ intentions to buy the investigated product category. The results from SEM-Logit show that attitude, subjective norms, perceived behavioral control, trust, loyalty, education and monthly income have significant impacts on intention to purchase cheeses with GIs. The findings of this research provide important contribution for understanding GI cheeses’ consumption intention and behavior.